2020
DOI: 10.1016/j.psj.2019.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative stress of oral administration of tea extract granule in chickens

Abstract: The present study was to evaluate antioxidative effect of tea extract granule ( TEG ) on oxidative stress induced by cyclophosphamide ( Cy ) in chickens. In experiment 1, chickens were randomly divided into 5 groups with 10 birds in each. Groups 3 to 5 were orally administered TEG in drinking water for 7 D at doses of 20, 40, and 80 mg/kg body weight, respectively. After that, groups 2 to 5 received intramuscular injection of Cy (100 mg/kg BW) for 3 D. Group 1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Similarly, MDA content can reflect the degree of lipid peroxidation; thereby, indirectly reflect cell damage and freshness of meat [41]. In agreement with our results, a diet with green tea extract led to a remarkably decreasing MDA content in meat tissue [42]. Polyphenols might be accumulated to exhibit antioxidant effects in meat tissues [35].…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 89%
“…Similarly, MDA content can reflect the degree of lipid peroxidation; thereby, indirectly reflect cell damage and freshness of meat [41]. In agreement with our results, a diet with green tea extract led to a remarkably decreasing MDA content in meat tissue [42]. Polyphenols might be accumulated to exhibit antioxidant effects in meat tissues [35].…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 89%
“…Chi et al observed that oral administration of tea saponins significantly increased T-AOC, SOD, CAT, GSH-PX, GSH, VC, and VE and enhanced the immune responses to Newcastle disease and infectious bronchitis vaccines in chickens with oxidative stress induced by cyclophosphamide [ 41 ]. They recently found that oral administration of tea extract granule (TEG) significantly increased T-AOC, SOD, CAT, GSH-PX, and GSH as well as decreased Carbonyl, LPO, and MDA [ 58 ]. EGCG has a characteristic structure with a large number of hydroxyl groups.…”
Section: Discussionmentioning
confidence: 99%
“…The homogenate was mechanically homogenized under the condition of ice water bath. The homogenate was centrifuged at 3,000 r/min for 10 min, and the supernatant was stored in a refrigerator at -20℃ until measured ( Chi et al, 2020 ). The concentrations of TP, ROS, T-AOC, CAT, MDA, SOD, H2O2 and GSH-Px were determined according to the instructions of the kit manufacturer.…”
Section: Methodsmentioning
confidence: 99%